问题 解答题
计算(能简便的用简便方法计算):
(1)(-16)-[(-5
1
3
)+(-3
2
3
)+(+3
1
7
)+(-2
1
7
)];
(2)1÷(1-
1
2
)÷(1-
1
3
)÷(1-
1
4
)÷(1-
1
5
)÷(1-
1
6
);
(3)(-
7
8
)÷(1
3
4
-
7
8
-
7
12
);
(4)
(-1)8×(-2)3-3×22÷[-1÷(-2)2]
0.25×22+[1-32×(-2)]

(5)(-98)×(-0.125)+(-98)×
1
8
-98×(-
4
7
).
答案

(1)原式=-16-(-9+1)=-16+9-1=-8;

(2)原式=1×2×

3
2
×
4
3
×
5
4
×
6
5
=6;

(3)原式=-

7
8
÷(
42
24
-
21
24
-
14
24
)=-
7
8
×
24
7
=-3;

(4)原式=

-8+12×4
1+19
=2;

(5)原式=(-98)×(-0.125+

1
8
-
4
7
)=(-98)×(-
1
8
+
1
8
-
4
7
)=-98×(-
4
7
)=56.

名词解释
判断题